Effects of a community resilience intervention program on victims of forced displacement: A case study (2021)
This article describes the effects of an intervention program that uses community resilience and the psychological, social, and subjective well-being of victims of forced displacement as a reference framework. Following a multiple instrumental case study methodology with pre–post-intervention measurements, the cases of eight people were analyzed, six women and two men between the ages of 30 and 65, low socioeconomic and educational level, all of whom had been victims of forced displacement and currently reside in Ibagué where the intervention program was performed. The reliable change index was applied to estimate the effects of the program. In each case, participation in the program significantly improved the results of certain variables, but there were differences between the cases concerning the improvement levels and intensity. Therefore, the development of programs that reinforce community resilience can have positive effects on the perceptions of the participants regarding their well-being and social relationships.